2022
DOI: 10.3389/fpsyg.2022.944838
|View full text |Cite
|
Sign up to set email alerts
|

A Biologically Inspired Neural Network Model to Gain Insight Into the Mechanisms of Post-Traumatic Stress Disorder and Eye Movement Desensitization and Reprocessing Therapy

Abstract: Eye movement desensitization and reprocessing (EMDR) therapy is a well-established therapeutic method to treat post-traumatic stress disorder (PTSD). However, how EMDR exerts its therapeutic action has been studied in many types of research but still needs to be completely understood. This is in part due to limited knowledge of the neurobiological mechanisms underlying EMDR, and in part to our incomplete understanding of PTSD. In order to model PTSD, we used a biologically inspired computational model based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 191 publications
(277 reference statements)
0
3
0
Order By: Relevance
“…However, how EMDR exerts its therapeutic action has been studied in many types of research but has yet to be fully understood. 17 In our case, the established protocol did not give the expected result; the desensitization by rapid eye movements of the traumatic events did not produce any change in the subjective perception of the disturbance in a first attempt following the steps of the protocol, which is; initiating desensitization through the traumatic event.…”
Section: Discussionmentioning
confidence: 54%
“…However, how EMDR exerts its therapeutic action has been studied in many types of research but has yet to be fully understood. 17 In our case, the established protocol did not give the expected result; the desensitization by rapid eye movements of the traumatic events did not produce any change in the subjective perception of the disturbance in a first attempt following the steps of the protocol, which is; initiating desensitization through the traumatic event.…”
Section: Discussionmentioning
confidence: 54%
“…This reduction in fear was accompanied by a decrease in neuronal excitability within circuits involving the basolateral amygdala ( 62 ), providing pioneering evidence of the neurobiological effects of EMDR in a murine model. Furthermore, Mattera and colleagues propose a neural network model in PTSD and EMDR therapy that involves four areas representing the role of sensory cortices, the hippocampus, the amygdala, and the PFC ( 63 ). Moreover, clinical studies in humans have demonstrated the effectiveness of EMDR therapy in treating various populations, including infants with post-traumatic stress symptoms ( 64 , 65 ), adults with post-traumatic stress disorder ( 66 , 67 ), and patients resistant to depression treatment ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…EMDR therapy helps to normalize their activity by facilitating the migration, processing, contextualization, integration, consolidation, or reconsolidation of traumatic memories (Harper et al, 2009 ; Pagani et al, 2011 , 2012 , 2017 ; Landin-Romero et al, 2018 ; Baek et al, 2019 ; Mattera et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%